2020
DOI: 10.1177/2233865919895854
|View full text |Cite
|
Sign up to set email alerts
|

Discussing the determinants of online budget transparency based on a spatial regression analysis of Croatian cities and municipalities: Do good neighbours make you better?

Abstract: Taxpayers want to pay as little in taxes as possible to fund an adequate level of public goods and services in their local government, and so they need to keep their local incumbents accountable. Online local budget transparency (OLBT) facilitates this accountability, as it enables citizens to find information online about their local budgets that is timely, accurate, comprehensive and understandable. The aim of this article is to identify the most important determinants of OLBT for all 556 Croatian cities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 68 publications
0
5
0
9
Order By: Relevance
“…In addition, the electoral turnout and the degree of political competition are deemed relevant factors since they can affect citizens' demands toward fiscal transparency and government accountability (i.e., agency theory approach). For instance, a high level of electoral participation would indicate that people are interested in public affairs, resulting in greater social demands for transparency and accountability (Mourao et al, 2020). Meanwhile, other authors point out that low voter turnout may threaten public organizations' legitimacy, so officials' transparency initiatives can emerge to restore public trust (i.e., legitimacy theory approach) (Tejedo-Romero & de .…”
Section: Data Description and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the electoral turnout and the degree of political competition are deemed relevant factors since they can affect citizens' demands toward fiscal transparency and government accountability (i.e., agency theory approach). For instance, a high level of electoral participation would indicate that people are interested in public affairs, resulting in greater social demands for transparency and accountability (Mourao et al, 2020). Meanwhile, other authors point out that low voter turnout may threaten public organizations' legitimacy, so officials' transparency initiatives can emerge to restore public trust (i.e., legitimacy theory approach) (Tejedo-Romero & de .…”
Section: Data Description and Methodologymentioning
confidence: 99%
“…For its part, legitimacy theory focuses on how politicians behave in order to legitimize their actions (Mourao, Bronić, & Stanić, 2020). In this regard, public officials are pressured to reveal information in order to clear up any doubts about their management, especially when they can be sanctioned, for example electorally, if they are judged as inefficient or corrupt.…”
Section: Some Concepts and Theoretical Models To Be Consideredmentioning
confidence: 99%
“…In contrast, with a less educated population, the most impoverished rural municipalities will have fewer monetary resources and fewer opportunities to attract high-income individuals. Finally, the theory of the neighboring effects (Mourao et al 2020;Mourao 2019) suggests that neighboring spaces exert a significant influence on the dimensions observed for a given sub-space, which can be thought as a derivation of the institutional isomorphism (DiMaggio and Powell 1983). Therefore, for the development of a space, it is needed that the surrounding sub-spaces also develop; otherwise, development gains of a given space will not last.…”
Section: Review Of the Literature On Fiscal Decentralization Policies...mentioning
confidence: 99%
“…For testing such hypotheses, we must refer to some models such as the spatial error model or the spatial lag model. We will include the variables that were previously analyzed in this paper (population density and the urban-metropolitan profile) as explanatory variables, following authors such as Stanic et al (2020) or Garcia-Rodriguez and Redmond (2020), who suggested that these variables are relevant proxies for sociocultural and institutional dimensions that spatially characterize the municipalities in fiscal terms. The descriptive statistics for these variables are available upon request.…”
Section: Fiscal Performance From the Perspective Of Population Densit...mentioning
confidence: 99%
“…Mesmo com as discussões singularizadas pelas variáveis, algumas menções dos resultados são importantes. Segundo a abordagem realizada pela Teoria de Agência no setor público, os prefeitos representam os agentes e a população os principais, e neste relacionamento podem existir conflitos de interesse conhecidos como problemas de agência, que podem ser solucionados por meio da transparência das ações dos gestores públicos (LI; NA, 2016; TEJEDO-ROMERO; ARAUJO, 2018;MOURÃO;BRONIĆ;STANIĆ, 2020;SUN;ANDREWS, 2020). Nesta perspectiva, o estudo apontou fatores capazes de serem utilizados para propiciar um maior nível de transparência fiscal dos municípios, fato que corrobora com a possibilidade de a transparência poder reduzir os conflitos de agência na gestão pública.…”
Section: Fatores Explicativos Da Transparência Fiscal Nos Municípios ...unclassified